2015
DOI: 10.3390/ma8125439
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Ferroelectric Ceramics for High Energy Density Capacitors

Abstract: With an ever increasing dependence on electrical energy for powering modern equipment and electronics, research is focused on the development of efficient methods for the generation, storage and distribution of electrical power. In this regard, the development of suitable dielectric based solid-state capacitors will play a key role in revolutionizing modern day electronic and electrical devices. Among the popular dielectric materials, anti-ferroelectrics (AFE) display evidence of being a strong contender for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
132
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(141 citation statements)
references
References 109 publications
4
132
0
2
Order By: Relevance
“…3(c) illustrates the capacitance C of PLZST10 versus E. At low field the value of C only increase slightly, but when E approaches 8kV/mm, the value of C grows rapidly due to the AFE-FE phase transition. 16,17 According to the expression of I max and equation (6), the increase of both E and C will result in a rise of increase rate of I max . Above 8 kV/mm, the field-induced FE phase becomes stable.…”
Section: Resultsmentioning
confidence: 99%
“…3(c) illustrates the capacitance C of PLZST10 versus E. At low field the value of C only increase slightly, but when E approaches 8kV/mm, the value of C grows rapidly due to the AFE-FE phase transition. 16,17 According to the expression of I max and equation (6), the increase of both E and C will result in a rise of increase rate of I max . Above 8 kV/mm, the field-induced FE phase becomes stable.…”
Section: Resultsmentioning
confidence: 99%
“…Antiferroelectrics display a field induced transition from antipolar to polar dielectric, and they have interesting properties such as the double hysteresis loop and large strains associated with it. These unique properties make antiferroelectric materials very attractive for technological applications involving high-energy supercapacitors [4][5][6][7][8], electrocaloric cooling [9], actuators [10], photovoltaic effects [11], and many other interesting dielectric phenomena. Very recently, experimental evidence of a novel four-state nonvolatile memory effect in antiferroelectrics was reported [12].…”
Section: Introductionmentioning
confidence: 99%
“…In this manner it is shown that even the diffusion of O vacancies at high dilution, 1%, in the simple cubic SrTiO 3 is far from the diffusion of dispersed isolated vacancies, but involves pairing and formation of larger complexes, possibly longer chains. It is clear that a knowledge of this type is necessary for improving the properties of ionic conductors, but the realistic cases of solid electrolytes for fuel cells, highly doped with acceptors in order to be made oxide or proton conductors, are predictably much more complicated than SrTiO 3 . From the large amount of information contained in the anelastic and dielectric spectra of such materials only a part can be interpreted in relatively direct manner, and much remains to be done.…”
Section: Discussionmentioning
confidence: 99%
“…Examples are the oxygen and proton conductors as solid electrolytes for fuel cells (SOFCs) [1], and the ferroelectric (FE) and antiferroelectric (AFE) compositions, which may find application in high energy capacitors for energy storage [2,3], efficient electrocaloric cooling [4], and electromechanical energy harvesting [5]. Figure 1 presents the cell of a cubic perovskite ABO 3 and ranges of different properties depending on the choice of the A and B cations. When the −6e charge of the ideally three O 2− atoms per unit cell is not fully compensated by the cation valence v A + v B , then V O are created and this can be exploited for creating a fast ion conductor.…”
Section: Introductionmentioning
confidence: 99%